The third sector and government in Australia: Not-for-profit reform under Labor, 2007–13 - Butcher, John (Taylor and Francis, 2015)
The emergence of ‘compacts’ between government and the ‘third’ or ‘not-for-profit’ sector is intimately linked to the comprehensive transformation of the welfare state. The first compacts in the United Kingdom in 1998 spawned similar policy instruments in other jurisdictions, including Australia. In 2006 the Labor opposition led by Kevin Rudd undertook to repair a ‘broken’ relationship between the federal government and the not-for-profit sector. The National Compact, launched in March 2010, was an initial step in a bumpy policy journey. Prime Minister Rudd was replaced in June 2010 by Julia Gillard, who portrayed the National Compact as the ‘foundation stone’ of a broader reform agenda. Although dogged by political instability, Gillard pursued ground-breaking reforms in the not-for-profit policy space. These reforms are now threatened with repeal by the Coalition government elected in 2013. This paper attempts to explain why Labor's reform agenda appears set to unravel.